2022
DOI: 10.35381/cm.v8i1.689
|View full text |Cite
|
Sign up to set email alerts
|

Teaching English vocabulary and online games to eighth grade students

Abstract: The objective is based on exploring the impact of the use of online educational games in comparison with traditional classroom methods to teach English vocabulary to eighth grade students at Mercedes Vázquez Correa School. Quantitative approach with a participation of 13 students. By means of a vocabulary retention test, results were obtained showing that students remember a greater amount of vocabulary by means of traditional methods; however, students remember a greater amount of words accurately with the us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…These findings align with the concept of "digital natives" proposed by Prensky (2001), which suggests that today's students are highly accustomed to technology. Therefore, the present investigation, as well as previous studies, promote its implementation to create a teaching and learning environment suitable for 21 st century students (Pintado-Peñaloza & Fajardo-Dack, 2022;Sadiku et al, 2017;Utku & Dolgunsöz, 2018).…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…These findings align with the concept of "digital natives" proposed by Prensky (2001), which suggests that today's students are highly accustomed to technology. Therefore, the present investigation, as well as previous studies, promote its implementation to create a teaching and learning environment suitable for 21 st century students (Pintado-Peñaloza & Fajardo-Dack, 2022;Sadiku et al, 2017;Utku & Dolgunsöz, 2018).…”
Section: Discussionmentioning
confidence: 65%
“…Moreover, the lack of motivation among students was very noticeable because they qualified English as something quite complex and boring because their teachers rarely used technology and focused primarily on teaching grammatical rules for writing sentences. The aforementioned problems were also found in other studies, which indicated that students struggled to learn vocabulary because it is tied to passive teaching methods that are not interesting, do not increase motivation, and require translation, fill-in-the-blanks activities, and word memorization (Alnatour & Hijazi, 2018;Derbouche & Hamadouche, 2016;Hasram et al, 2021;Pintado-Peñaloza & Fajardo-Dack, 2022;Romero et al, 2023).…”
Section: Introductionmentioning
confidence: 65%